Training and Development Needs of Early Childhood Educators for Effective Instructional Delivery in Awka-South Local Government Area, Anambra State Nigeria - Chinyere, Umeji Ifeoma (Social Education Research, 2023)
This study investigated the training and development needs of early childhood educators for effective instructional delivery in Awka South Local Government Area, Anambra State, Nigeria. Two hypotheses and three research questions guided the study. Data were collected using a questionnaire titled Training and Development Needs Scale (TDNS), which was administered to 130 early childhood educators. The acquired data were examined at a significance level of 0.05 using the independent t-test, mean, and standard deviation. Results indicated that early childhood educators needed training in managing the classroom and school to deliver education effectively. The study also showed that early childhood educators require support for practical workshops on contemporary pedagogies to provide teaching effectively. Consequently, training and development empower educators to provide children with a high-quality education. It was suggested that the government hold educator training programs regularly. Such programs must deal with subject matter, the utilization of teaching aids, lesson planning and delivery, classroom management, and student evaluation.